2017
DOI: 10.1007/s10103-017-2171-4
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond, wettability and AFM evaluations on CO2 laser-irradiated CAD/CAM ceramic surfaces

Abstract: The purpose of this study is to determine the CO laser irradiation in comparison with sandblasting (Sb), hydrofluoric acid (Hf) and silane coupling agent (Si) on shear bond strength (SBS), roughness (Rg) and wettability (Wt) of resin cement to CAD/CAM ceramics. Sixty (CAD/CAM) ceramic discs were prepared and distributed into six different groups: group A, control lithium disilicate (Li); group B, control zirconia (Zr); group C, Li: CO/HF/Si; group D, Li: HF/Si; group E, Zr: CO/Sb/Si; group F, Zr: Sb/Si. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
1
15
0
2
Order By: Relevance
“…The data here reported, according to Gamal et Al [32] confirmed that ceramic laser-irradiated surfaces found to be very low, thus explaining the few damages evidenced and, overall, the poor 249 modifications in the ceramic structure, as shown by the EDS analysis.…”
supporting
confidence: 69%
“…The data here reported, according to Gamal et Al [32] confirmed that ceramic laser-irradiated surfaces found to be very low, thus explaining the few damages evidenced and, overall, the poor 249 modifications in the ceramic structure, as shown by the EDS analysis.…”
supporting
confidence: 69%
“…Several studies used CO 2 laser irradiation to increase the roughness of the ceramic surfaces and improve the bond strength to the resin . However, controversial results were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Lasers have been introduced during the last decade as an alternative to traditional methods for ceramic surface treatment. Numerous works have investigated the effects of CO 2 lasers in continuous or long pulse mode, on shear bond strength of ceramic to other substrates [ 20 , 21 ]. Short pulse lasers such as Nd:YAG, Er:YAG, and Er,Cr:YSGG have also been tested [ 22 – 24 ].…”
Section: Introductionmentioning
confidence: 99%